Maximizing Profit Margins: The Interconnection Between Working Capital Efficiency and Sales Growth - Purba, Jamian; Wulandari, Dian Sulistyorini; Djatnicka, Erlina Widayanti (Pusat P2M Politeknik Negeri Batam, 2025)
This study explores the influence of working capital efficiency on profitability, emphasizing the moderating role of sales growth. Utilizing panel data from publicly listed companies in food and beverage companies listed on the Indonesia Stock Exchange for the 2018-2021 period, the research employs multiple linear regression analysis to assess the direct impact of working capital efficiency, measured by the Working capital efficiency, on profitability, measured by Return on Assets (ROA). The analysis further incorporates sales growth as a moderating variable to evaluate its interaction with working capital efficiency. The findings confirm a positive relationship between working capital efficiency and profitability, underscoring the importance of optimizing current asset and liability management. Additionally, the results demonstrate that sales growth significantly moderates this relationship, amplifying the positive impact of working capital efficiency on profitability. Firms experiencing robust sales growth benefit more from efficient working capital practices, as higher revenues enhance liquidity and resource utilization. Conversely, firms with stagnant or declining sales face limitations in leveraging the benefits of working capital optimization. This research contributes to the existing literature by highlighting the dynamic interplay between working capital efficiency and sales growth, offering a nuanced perspective on profitability determinants. The findings provide actionable insights for managers, suggesting a dual-focus strategy of enhancing working capital efficiency and fostering sales growth to maximize financial performance. Future studies could expand on this framework by exploring additional moderating variables, sector-specific dynamics, and long-term implications in diverse economic contexts.